Pengembangan Media Pop-Up Book IPAS Berbasis Living Values Education Program untuk Peserta Didik SD - Harwati, Tantri; Apriani, An-Nisa; Sari, Indah Perdana; Shidiq, Galih Albarra (Alma Ata University Press, 2024)
Religious character is important to be applied from an early age to prevent moral decadence. Inserting or incorporating religious characters can be done in learning activities by using learning media. Pop-up book media is a book-shaped media with a real-like image display and can move. Meanwhile, LVEP is a value education that offers value activities so that students are able to explore and develop life values. The purpose of this research is to produce LVEP-based IPAS pop-up book media to improve religious character, teacher and student responses to the media. LVEP-based IPAS pop-up book media uses the 4D model which goes through 4 stages, namely the defining stage (define), the planning stage (design), the development stage (development), and the dissemination stage (disseminate). The data collection technique is qualitative from the results of interviews and quantitative data from the validation of material experts, media experts and teacher and student responses. Interviews were conducted with one class teacher, validation by one material expert, one media expert and 9 students. On the validation of the material that gets an average score of 4.6 with the category